Rotational K?-translators in Minkowski Space - Aydin, Muhittin Evren; Lopez, Rafael (Mathematical Soc Rep China, 2023)
A spacelike surface in Minkowski space R31 is called a Ka-translator of the flow by the powers of Gauss curvature if satisfies Ka =< N,v(->)>, alpha not equal 0, where K is the Gauss curvature, N is the unit normal vector field and.v is a direction of R-1(3). In this paper, we classify all rotational K-alpha-translators. This classification will depend on the causal character of the rotation axis. Although the theory of the Ka-flow holds for spacelike surfaces, the equation describing K-alpha-translators is still valid for timelike surfaces. So we also investigate the timelike rotational surfaces that satisfy the same prescribing Gauss curvature equation.
Keywords: Minkowski space; K-alpha-translator; surfaces of revolution